2009
DOI: 10.1016/j.stem.2009.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Cdk4/CyclinD1 Overexpression in Neural Stem Cells Shortens G1, Delays Neurogenesis, and Promotes the Generation and Expansion of Basal Progenitors

Abstract: During mouse embryonic development, neural progenitors lengthen the G1 phase of the cell cycle and this has been suggested to be a cause, rather than a consequence, of neurogenesis. To investigate whether G1 lengthening alone may cause the switch of cortical progenitors from proliferation to neurogenesis, we manipulated the expression of cdk/cyclin complexes and found that cdk4/cyclinD1 overexpression prevents G1 lengthening without affecting cell growth, cleavage plane, or cell cycle synchrony with interkinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
479
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 510 publications
(523 citation statements)
references
References 45 publications
40
479
2
2
Order By: Relevance
“…5). These results are also consistent with the longer G1 observed in rapamycin-treated neural stem cells Alterations in the precise length of G1 phase in stem cells have been correlated with defects in differentiation (Lange et al 2009;Li et al 2012). In summary, our in vitro results indicate that rapamycin inhibits neural progenitor proliferation and differentiation.…”
Section: Rapamycin But Not Metformin Reduces Neuronal Differentiationsupporting
confidence: 89%
“…5). These results are also consistent with the longer G1 observed in rapamycin-treated neural stem cells Alterations in the precise length of G1 phase in stem cells have been correlated with defects in differentiation (Lange et al 2009;Li et al 2012). In summary, our in vitro results indicate that rapamycin inhibits neural progenitor proliferation and differentiation.…”
Section: Rapamycin But Not Metformin Reduces Neuronal Differentiationsupporting
confidence: 89%
“…Recently, Lange et al [40] demonstrated that forcing the lengthening of G 1 is sufficient to promote the exit of the cell cycle of cortical progenitors and their differentiation into projection neurons. As our data support an increased rate of precursor cell cycle exit in Cdk6 À/À neurogenic regions, we compared the length of G 1 in Cdk6-knockout and WT animals.…”
Section: Cdk6 2/2 Neural Precursors Prematurely Exit the Cell Cycle Amentioning
confidence: 99%
“…As our data support an increased rate of precursor cell cycle exit in Cdk6 À/À neurogenic regions, we compared the length of G 1 in Cdk6-knockout and WT animals. To this aim, we performed cumulative S-phase labeling with BrdU [18,40] (Fig. 6A-6D).…”
Section: Cdk6 2/2 Neural Precursors Prematurely Exit the Cell Cycle Amentioning
confidence: 99%
“…By impairing stem cell division even mildly, the proportion of symmetric divisions is concomitantly reduced, depleting the progenitor pool and limiting the total number of neurons that can be generated (Thornton & Woods, 2009; Alcantara & O'Driscoll, 2014). On the other hand, altering the cell cycle length, in particular the G1 phase, contributes to switching of neural progenitors from proliferative to differentiating states (Calegari et al , 2005; Lange et al , 2009; Li et al , 2011). …”
Section: Introductionmentioning
confidence: 99%